Biometry and corneal aberrations after cataract surgery in childhood. (16th May 2022) - Hansen, Mathias Møller; Bach‐Holm, Daniella; Kessel, Line
Abstract: Background: To report long‐term biometric and refractive outcomes in a group of Danish children after surgery for childhood cataract. Methods: Children between 7 and 18 years who had undergone uni‐ or bilateral cataract surgery at the Department of Ophthalmology, Rigshospitalet, Denmark, were examined in this cross‐sectional study. Swept source optical coherence tomography (OCT) based optical biometry (IOLmaster 700) and anterior tomography (Pentacam) was performed. Healthy fellow eyes from those with unilateral cataract were used as controls. Results: We included 56 children in the study with a median age at surgery of 43.8 months (1.6–137.6). The amount of higher order aberrations was significantly increased in operated eyes (median root mean square 0.461 μm [range 0.264–1.484]) compared with non‐operated eyes (median root mean square 0.337 μm [range 0.162–0.498], p  < 0.001). Younger age at surgery was positively associated with more higher order aberrations at follow‐up ( p  < 0.001), but we found no significant associations between the amount of higher order aberrations and visual acuity or contrast vision. Longer axial length was associated to glaucoma while shorter axial length was associated to strabismus ( p  < 0.001). Conclusions: Eyes operated for childhood cataract have higher order aberrations compared with non‐operated eyes. Higher order aberrations are complex refractive errors that cannot be corrected by normal lenses and may contribute to poor visual outcomes for the children. We found an association between young age at surgery and higher order aberrations.